Philippine Transport Infrastructure Development Roadmap Framework Plan : Executive Summary - Cambridge Systematics (World Bank, Washington, DC, 2015)
Various transport-related agencies and local governments develop their respective transport plans or strategies to address bottlenecks and improve outcomes in the transport sector. However, to be able to bring a more focused or targeted intervention that is more inclusive, these various strategies need to focus on establishing interconnectivity between key urban growth centers and between lagging and fast-growing regions, and creating supporting institutions that promote greater integration. Upon the request of the National Economic and Development Authority, a framework plan was developed to provide policy-makers with a strategic framework to help identify the transport needs of the Philippines and guide in implementing an integrated, more coordinated approach to establishing stronger transport infrastructure linkages to support the country’s inclusive growth agenda. The framework plan was developed under the guidance of a vision and goals developed by stakeholders across the Philippines. This comprehensive vision can be summarized as ‘Bringing us all closer together for prosperity.’ The geographic focus of the Framework Plan includes all of the Philippines outside of Metro Manila. This Framework Plan does not replicate the work being done by the Japan International Cooperation Agency (JICA) for Metro Manila (the JICA study covers Metro Manila with an approximate radius of 100 kilometers and is being conducted to evaluate specific transport infrastructure projects for the Metro Manila area). Future improvements and needs of transportation infrastructure to meet the demand for long-distance transport to and from Metro Manila and to other urban/economic centers in the Philippines are considered; nevertheless, national-level strategies recommended in this study affect all areas of the Philippines.